Effects of different sodium concentrations in replacement fluids during prolonged exercise in women. Issue 4 (31st July 2003) - Twerenbold, R; Knechtle, B; Kakebeeke, T H; Eser, P; Müller, G; von Arx, P; Knecht, H
Abstract : Objective: To investigate the effect of different sodium concentrations in replacement fluids on haematological variables and endurance performance during prolonged exercise. Methods: Thirteen female endurance athletes completed three four hour runs on a 400 m track. Environmental conditions differed between the three trials: 5.3°C and snow (trial 1), 19.0°C and sunny weather (trial 2), 13.9°C and precipitation (trial 3). They consumed 1 litre of fluid an hour during the trials with randomised intake of fluids: one trial (H) with high sodium concentration (680 mg/l), one trial (L) with low sodium concentration (410 mg/l), and one trial with only water (W). Before and after the trials, subjects were weighed and blood samples were taken for analysis of [Na + ]plasma, packed cell volume, and mean corpuscular volume. Results: The mean (SD) decrease in [Na + ]plasma over the whole trial was significantly (p<0.001) less in trial H (2.5 (2.5) mmol/l) than in trial W (6.2 (2.1) mmol/l). Mild hyponatraemia ([Na + ]plasma = 130–135 mmol/l) was observed in only six women (46%) in trial H compared with nine (69%) in trial L, and 12 (92%) in trial W. Two subjects (17%) in trial W developed severe hyponatraemia ([Na + ]plasma <130 mmol/l). No significant differences were found in performance or haematological variables with the three different fluids. There was no significant correlation between[Na + ]plasma after the run and performance. There was a significant correlation between changes in [Na + ]plasma and changes in body weight. Conclusions: Exercise induced hyponatraemia in women is likely to develop from fluid overload during prolonged exercise. This can be minimised by the use of replacement fluids of high sodium concentration. Sodium replacement of at least 680 mg/h is recommended for women in a state of fluid overload during endurance exercise of four hours. However, higher [Na + ]plasma after the run and smaller decreases in [Na + ]plasma during the trials were no indication of better performance over four hours.